Home country versus cross-border negative externalities in barge banking organization failures and how to avoid them - Robert A. Eisenbeis (Federal Reserve Bank of Atlanta, 2006)
This paper examines the negative externalities that may occur when a large bank fails, describes the nature of those externalities, and explores whether they may be greater in a case involving a large cross-border banking organization. The analysis suggests that the chief negative externalities are associated with credit losses and losses due to liquidity problems, and these losses are critically affected by how promptly an insolvent institution is closed, how quickly depositors gain access to their funds, and how long it takes borrowers to reestablish credit relationships. While regulatory delay and forbearance may affect the size and distribution of losses, the likely incident of systemic risk and the negative externalities are more associated with the structure of the applicable bankruptcy laws and methods available to resolve a failed institution and quickly get it operating again. This circumstance implies that regulatory concerns about systemic risk should be directed first at closing institutions promptly, reforming bankruptcy statutes to admit special procedures for handling bank failures, and providing mechanisms to give creditors and borrowers prompt and immediate access to their funds and lines of credit.
Keywords: G28; G33; G38; D74; D83; G21; 330; cross-border banking; financial crises; bankruptcy; branching; banking subsidiaries; supervision and regulation